Socioeconomic Stability and Variability in Stock Market Prices: A Case Study of Karachi Stock Exchange - Ali, Rafaqat; Khan, Rana Ejaz Ali (Asian Journal of Economic Modelling, 2018)
The study attempted to identify the factors that responsible for variability in stock market prices in Karachi Stock Exchange particularly focusing on socioeconomic stability in the country. The socioeconomic stability is measured by an index including social, economic and political dimensions of stability. Annual time series data for the years 1973-2012 is utilized, and Phillips & Perron (PP) test is employed for stationarity. Autoregressive Conditional Heteroscedasticity and Generalized Conditional Heteroscedasticity (ARCH/GARCH) technique are used for volatility in stock market prices. For the structural breaks, Chow test is applied. Finally, the study utilized the Autoregressive Distributed Lag (ARDL) approach to estimate the long-run and short-run dynamic relationship. The results indicate that inflation, exchange rate, and foreign direct investment positively influence the stock price volatility. Socioeconomic stability negatively affects the volatility in stock market prices in both short-run and long-run. The country should improve socioeconomic stability by attaining economic, social and political standards in the country.